Discrete Aurora on the Nightside of Mars: Occurrence Location and Probability. Issue 3 (24th February 2022) - Fang, Xiaohua; Ma, Yingjuan; Schneider, Nick; Girazian, Zach; Luhmann, Janet; Milby, Zachariah; Jain, Sonal; Dong, Yaxue; Curry, Shannon; Jakosky, Bruce
Abstract: This paper represents the first attempt to predict the occurrence location and probability of discrete electron aurora on the nightside of Mars. We run a 3‐D time‐dependent magnetohydrodynamic model to characterize the spatial and temporal dynamics of magnetic field and plasma distributions over the course of one planetary rotation. We perform eight simulation cases under solar minimum quiet‐solar‐wind conditions (four equinox/solstice seasons, each with two interplanetary magnetic field polarities) and in an actual interplanetary coronal mass ejection (ICME) case to assess quiet and space weather situations, respectively. The occurrence of detectable discrete aurora is subject to the combination of the probabilities that (a) the ionosphere is magnetically connected with high altitudes through open field lines and (b) precipitating energy fluxes of >30 eV electrons exceed 0.1 erg/cm 2 /s. Our results show that during quiet solar activity, discrete aurora occurs likely on small‐scale patches embedded inside strong crustal magnetic field regions (with a magnitude greater than 50 nT at 150 km), and the overall chance across the globe is ∼0.77%. The higher probability over strong crustal field regions is attributed to the stronger magnetic field convergence. Modeling shows the occurrence probability dramatically increases during the ICME event, particularly by more than an order of magnitude in weak crustal field regions. Our model results reasonably agree with NASA Mars Atmosphere and Volatile EvolutioN and Mars Express observations. Our study suggests that nightside discrete electron aurora is not caused by the direct entry of magnetosheath plasma in a cusp‐like process but due to the recycling of nightside magnetospheric electrons. Plain Language Summary: This paper represents the first attempt to predict the occurrence location and probability of discrete electron aurora at Mars on a planetary scale. Discrete aurora is a patchy and sporadic phenomenon, posing a daunting challenge for understanding how and where auroral electron precipitation takes place in the ionosphere. To address this challenge, we apply a state‐of‐the‐art global model to characterize the spatial and temporal dynamics of near‐Mars plasma and magnetic field environments. We simulate the penetration of energetic electrons from high altitudes to the nightside ionosphere through open magnetic field lines, a process responsible for auroral emissions. Our results show that during quiet solar activity, the overall chance of observing a discrete auroral event on the nightside is only ∼0.77% across the globe, but the odds are significantly higher over strong crustal field regions. The occurrence probability is enhanced globally during an extreme space weather event, especially in weak crustal field regions. This study reveals a different source mechanism from the prevailing hypothesis that discrete aurora may be excited by the direct entry of magnetosheath plasma in a cusp‐like process. Instead, we propose that it is caused by the recycling of nightside magnetospheric electrons that return to the ionosphere. Key Points: Modeling shows that discrete aurora occurs more likely on small‐scale patches embedded inside strong crustal field regions Auroral occurrence probability greatly increases during space weather events, particularly in weak crustal field regions Discrete aurora is not caused by the direct entry of magnetosheath plasma but due to the recycling of nightside magnetospheric electrons